Evaluation of diversity in some genotypes of Algerian durum wheat using agronomical and biochemical markers - Aicha Atoui; Leila BOUDOUR; Ghania Chaib; Nabil BOUDERSA (Society for Indonesian Biodiversity, 2021)
Abstract. Atoui A, Boudour L, Chaib G, Nabil B. 2021. Evaluation of diversity in some genotypes of Algerian durum wheat using agronomical and biochemical markers. Biodiversitas 22: 2005-2011. In Algeria, wheat occupies a preponderant place regarding its food richness, and its agronomic characteristics. Quantification and characterization of the local genetic material of different species constitute a strategic axis for the improvement of these species. To quantify the diversity that may exist between nine genotypes belonging to the durum variety “valenciae” mainly cultivated in Algeria, biochemical and agronomical parameters were studied. The obtained results revealed highly significant differences for all measured agronomical parameters and a significant positive relationship between grain yield and its compounds. Protein profiles obtained using SDS-PAGE allowed us to split the total seed proteins. The obtained gel has shown different bands with molecular weights ranging from 17 to 122.09 KDa of which ten monomorphic bands, eight polymorphic bands and Three Unique bands in G6 and G9. The total protein polymorphism revealed an intra-varietal variability. This study will help breeders better select genotypes to be used in the Algerian wheat breeding program.